Transcriptome analysis identifies candidate genes in the biosynthetic pathway of sex pheromones from a zygaenid moth, Achelura yunnanensis (Lepidoptera: Zygaenidae) - Nuo, Shu-Mei; Yang, An-Jin; Li, Gen-Ceng; Xiao, Hai-Yan; Liu, Nai-Yong (PeerJ, 2021)
In most moth species, sex pheromones responsible for mating and communication of both sexes are primarily produced by the pheromone glands (PGs) of female moths. Although the PG transcriptomes and pheromone production related genes from 24 moth species have been characterized, studies on the related information remain unknown in the Zygaenidae family. Here, we sequenced the PG transcriptome of a zygaenid moth, Achelura yunnanensis. Such the sequencing resulted in the yields of 47,632,610 clean reads that were assembled into 54,297 unigenes, coupled with RNA sequencing data from 12 other tissues. Based on the transcriptome, a total of 191 genes encoding pheromone biosynthesis and degradation enzymes were identified, 161 of which were predicted to have full-length sequences. A comparative analysis among 24 moth species of nine families indicated that the numbers of the genes were variable, ranging from 14 in two Grapholita species to 191 in A. yunnanensis. Phylogenetic analysis in parallel with the expression data highlighted some key genes, including three △9 and four △11 desaturases, four fatty acyl-CoA reductases (FARs) clustering in the pgFAR clade, and three significantly antennae-enriched aldehyde oxidases. An extensive tissue- and sex- expression profile revealed a broad distribution of the genes, in which 128 relatives were detected in the PGs and 127 in the antennae. This study reports, for the first time, the gene repertoires associated with the pheromone production in Zygaenidae, and provides a valuable resource for exploring putative roles of the PG-enriched genes in A. yunnanensis.
Keywords: Achelura yunnanensis; Pheromone gland; Transcriptome; Pheromone biosynthesis gene; Pheromone degradation gene